UN international legal instruments in the context of solving the global problem of refugees and migrants - Liubov Zhvanko (Європейські історичні студії, 2019)
The article analyzes the most recent challenge of the 21st century. – a steady increase in the number of displaced persons. The author first analyzed the “modification” of the causes of their appearance during the XX – XXI centuries from the classic – two world wars to the new – environmental and man-made disasters. It is proved that this problem belongs to the global problems of mankind, and therefore requires a search for the highest-level solution to the UN resolutions. Because it is impossible to overcome at least today, the community has embarked on a path of control and regulation, for which the Global Compact on Safe, Organized and Regulated Migration and the Global Refugee Treaty were adopted in 2018 at the UN level. The author concludes that the Global Compact on Safe, Organized and Regulated Migration and the Global Refugee Treaty are, in fact, the first step in the efforts of at least the first attempts to resolve the case, but their declarative nature casts doubt on the possibility of solving this global problem. The problem of internally displaced persons in Ukraine, the emergence of which was the result of the Russian Federation’s war against Ukraine and the inability at present to join our state to implement the provisions of the above documents, was stressed separately.